Hubungan Antara Persepsi Terhadap Lingkungan Psikologis Kerja Dengan Loyalitas Kerja Pada Karyawan PT. Djitoe Indonesian Tobacco Surakarta - Kumala, Azarachma Ulfi; , Susatyo Yuwono, S.Psi.,M.Si,Psi (2017)
The purpose in this research is to know the relation between perception toward psychological work environment with work loyalty, and hypothesis in this research is a positive relation between perception toward psychological work environment with work loyalty on PT. Djitoe Indonesian Tobacco Surakarta's employees. This research's subjects were production employees. This research used quantitative method with perception toward psychological work environment scale and work loyalty scale. The data analysis technique in this research used correlation of Carl Pearson' Product Moment with SPSS 16.0 program for windows. Based on the result of data analysis, the correlation coefficient (r) of 0,594; significant (p) = 0,000 (p < 0,01) means that there is a positive corelation between perception toward psychological work environment with work loyalty on PT. Djitoe Indonesian Tobacco Surakarta's employees. Effective contribution by perception toward psychological work environment is 35,3%, the rest is 64,7% is influence by the other factors. Work loyalty variable have the empirical means (EM) is 51,94 and the hypothetical means (HM) is 42,5 which means that work loyalty variable get in to high category. Then perception toward psychological work environment have the empirical means (EM) is 46,03 and the hypothetical means (HM) is 40 which means that variable perception toward psychological work environment get in to high category. Keywords: perception toward psychological work environment, work loyalty, employees